Renoprotective effects of coenzyme Q10 supplementation in patients with chronic kidney disease: a protocol for a systematic review - Hisashi Noma; Takeshi Hasegawa; Hiroki Nishiwaki; Erika Ota; Taihei Suzuki; Yoshitaka Watanabe; Yoshifusa Abe (BMJ Open)
Introduction Coenzyme Q10 (CoQ10) is a fat-soluble vitamin-like quinone. The plasma levels of CoQ10 are reduced in patients with chronic kidney disease (CKD). CoQ10 supplementation can improve mitochondrial function and decrease oxidative stress in these patients. This systematic review will assess the renoprotective effects of CoQ10 supplementation in patients with CKD.Methods and analysis We will include the following studies: (1) randomised-controlled trials, (2) participants with CKD and (3) participants treated with CoQ10 as an intervention. The systematic review protocol was prepared in accordance with the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols. MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials and International Clinical Trials Register databases will be searched for articles without language restrictions in December 2024. The authors will be divided into two groups. Two independent authors will screen the titles and abstracts of all reports extracted via an electronic search. After the initial screening, the authors will independently review the full-text articles and perform a directed content analysis of the extracted data. For outcomes measured using continuous scales of measurement, we will adopt standardised mean differences as the effect measures. We will pool the data using the random‐effects model.Ethics and dissemination No human participants will be involved in the study. On completion of the analysis, the manuscript will be prepared for publication in a peer-reviewed journal.PROSPERO registration number CRD42021241085.